Orthosiphon stamineus Benth (Uses and Bioactivities) - Marina Silalahi (Indonesian Journal of Science and Education (IJOSE), 2019)
Orthosiphon stamineus Benth., or kumis kucing is a the medicinal plants have been used as diuretic medicine. The utilization of medicinal plants associated to its secondary metabolite. This article aims to explain uses pf the O. stamineus and the its secondary metabolites. This article is based on literature offline and online media. Offline literature used the books, whereas online media used Web, Scopus, Pubmed, and scientific journals. Orthosiphon stamineus has two varieties called purple varieties (which have purple-colored flowers) and white varieties (which have white-colored flowers). Some of secondary metabolites in the O. stamineus are the terpenoids, phenols, isopimaran type ispenimoids, flavonoids, benzochromes, and organic acid derivatives. The traditional medicine of the Orthosiphon stamineus uses as the diuretic, hypertension, hepatitis, jaundice, and diabetes mellitus. Keywords: Orthosiphon stamineus, diuretics, diterpenoids, hypertension